The unitary executive presidential power from Washington to Bush - Calabresi, Steven G.; Yoo, Christopher S. (New Haven, Conn. ; London : Yale University Press, 2008)
This is a detailed historical and legal examination of presidential power and the theory of the unitary executive. This theory, that the American Constitution gives the president the power to remove and control all policy-making subordinates in the executive branch, has been the subject of heated debate since the Reagan years.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Executive power -- United States -- History; Presidents -- United States -- History; United States -- Politics and government; History; United States of America, USA; History of the Americas